2009
DOI: 10.1007/s00464-009-0374-x
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic cholecystectomy for acute cholecystitis: safe implementation of successful strategies to reduce conversion rates

Abstract: This study demonstrated that, with specific strategies to decrease conversion and with technical improvements, the conversion rates can be decreased with no demonstrable difference in postoperative complications. Gallbladder wall thickness and increasing age are risk factors for conversion to open surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 18 publications
1
20
0
1
Order By: Relevance
“…A thickened gallbladder wall was considered a significant risk in 9 of these studies [10,30,33,[35][36][37][40][41][42] . Meta-analysis on 3 of the studies [33,35,42] (n = 1,814, median NOS = 7 (range 7-8), I 2 = 0) found a pooled OR of 8.17 (95% CI 5.38-12.40; fig. 2 g), suggesting that a gallbladder wall thicker than 4-5 mm on preoperative ultrasound was a risk factor for conversion.…”
Section: Gallbladder Wall Thicknessmentioning
confidence: 99%
See 2 more Smart Citations
“…A thickened gallbladder wall was considered a significant risk in 9 of these studies [10,30,33,[35][36][37][40][41][42] . Meta-analysis on 3 of the studies [33,35,42] (n = 1,814, median NOS = 7 (range 7-8), I 2 = 0) found a pooled OR of 8.17 (95% CI 5.38-12.40; fig. 2 g), suggesting that a gallbladder wall thicker than 4-5 mm on preoperative ultrasound was a risk factor for conversion.…”
Section: Gallbladder Wall Thicknessmentioning
confidence: 99%
“…Older age was found to be a significant risk factor in 16 studies [8,11,25,27,30,32,34,36,[41][42][43][44][45][46]48] . Meta-analysis on 4 of these studies [33][34][35]39] (n = 2,820, median NOS = 8 (range 7-9), I 2 = 0%) found a pooled OR of 1.64 (95% CI 1.22-2.19; fig.…”
Section: Risk Factors For Conversion Of Laparoscopic Cholecystectomy mentioning
confidence: 99%
See 1 more Smart Citation
“…There was no significant difference in conversion rate, mortality, morbidity and postoperative hospital stay between the three studied groups. In Low et al [22] the mean time from symptoms to surgery in patients who had successful ELC was 5.72 ±4.6 days and it was 5.83 ±1.73 days for patients who were converted to open procedure. Ohta et al [23] compared 4 timing groups of LC (72 hours, 4-14 days, 3-6weeks, and.6weeks after onset of symptoms) and found that the best timing for LC for acute cholecystitis is within 72 hours.…”
Section: Postoperative Hospital Staymentioning
confidence: 96%
“…Despite improved surgical technology and increased surgical skills with laparoscopic technique, conversion rates of up to 10% continue to be reported. [7][8][9][10][11][12][13][14] Several patient-related factors have been identified that are associated with increased risk of conversion, including male gender and older age. 11,[15][16][17] Intraoperative factors, however, are the final determinant of why a surgeon converts a laparoscopic case to open.…”
mentioning
confidence: 99%